(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Heavy metal contamination of water systems remains a critical environmental challenge due to its persistence, toxicity and bio-accumulative nature. This study investigates the potential of activated carbon derived from mango (Mangifera indica) seed coats as a low cost and sustainable adsorbent for the removal of cadmium (Cd2+) ions from aqueous solutions. The adsorbent was prepared via carbonization followed by chemical activation and characterized using Fourier Transform Infrared Spectroscopy (FTIR), which revealed the presence of functional groups such as hydroxyl and carbonyl responsible for metal binding. Batch adsorption experiments were conducted to evaluate the effects of operational parameters, including initial metal ion concentration (10 to 50 mg/L) and adsorbent dosage (0.1 to 0.5 g) at an optimized pH of 5. The results indicated that adsorption efficiency decreased with increasing Cd2+ concentration, reaching a maximum removal efficiency of about 81.00 % at 10 mg/L. Furthermore, increasing adsorbent dosage beyond 0.1 g resulted in only marginal improvements due to possible site overlap and particle aggregation, identifying 0.1 g as the optimal dosage. Equilibrium data were best described by the Freundlich isotherm model, indicating heterogeneous surface adsorption, while kinetic studies showed that the adsorption process followed pseudo second order kinetics, suggesting chemisorption as the dominant mechanism. The adsorption process was governed by electrostatic interactions, ion exchange, and surface complexation. The study demonstrates that mango seed coat derived activated carbon is an effective, eco-friendly and economically viable alternative for Cd2+ removal. This work highlights the dual benefits of agricultural waste valorization and sustainable water treatment, making it particularly relevant for resource limited environments.